P29 Dietary zinc depletion worsens the outcome of acute myocardial ischaemia. (26th October 2016) - Skene, K; Walsh, SK; Burrows, C; Meier, P; Gordon, MJ; Beattie, J; Wainwright, CL
Abstract : Zinc (Zn) supplementation in acute myocardial ischaemia and reperfusion (I/R) is cardioprotective, however the effect of dietary Zn deficiency on I/R outcomes is unknown. Furthermore, Zn deficiency leads to VSMC apoptosis, but its effect on vascular function has not been determined. The aims of this study were therefore to determine the effect of a Zn deficient diet in rats on the outcome of I/R and ex vivo vascular function. Male rats were allocated to one of three groups: 1) Zn adequate (ZA) diet (35mg Zn/kg) fed ad libitum; 2) Zn deficient (ZD) diet (<1 mg Zn/kg); and 3) ZD Pair-fed controls (PF). Isolated hearts from all rats were subjected to 30min regional ischaemia followed by 2h reperfusion and vascular function was assessed using wire myography. Hearts from rats fed a ZD diet exhibited a larger infarct size compared to both ZA and PF animals. Conversely, hearts from both ZD and PF rats exhibited fewer arrhythmias compared to ZA rats, suggesting that while Zn deficiency worsens tissue injury the effect on arrhythmias is likely due to the reduced calorie intake rather than Zn deficiency per se. Blood vessels from Zn deficient rats responded normally to both contractile and relaxant agents. In contrast, acute Zn depletion (induced in vitro by TPEN) reduced the contractile response to U46619 and relaxant responses to both SNP and MCh. Dietary Zn restriction is associated with a worsening of myocardial injury in response to acute I/R, with no apparent effects on electrical rhythm disturbances or vascular function.